Training of health care workers in adherence counselling for comprehensive care, management and treatment clinics - Raphela, Ramadimetja Elsie (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.